An Extensive Analysis of Computer-Aided Drug Design for Novel Psychotropic and Neurological Substances - Satish Kumar Yadav; Mohd. Wasiullah; Piyush Yadav; Safiya Sajid; Ms. Anjali Maurya (International Journal of Brain Sciences, 2024)
A comprehensive review of the use of computer-aided drug design (CADD) in the creation of innovative neurologic and neuropsychiatric medications is given in this article. It discusses the challenges in traditional drug discovery approaches and highlights the role of computational methods in accelerating the identification and optimization of drug candidates targeting psychiatric and neurological disorders. The method of finding new drugs has been completely transformed by Computer-Aided Drug Design (CADD), which combines medicinal chemistry concepts with computer tools. This review explores the applications of CADD in the development of psychotropic and neurological drugs. Beginning with an overview of psychotropic and neurological disorders, the article delves into the challenges faced in traditional drug discovery methods. It then elucidates the principles and methodologies of CADD, including molecular docking, pharmacophore modeling, and quantitative structure-activity relationship (QSAR) analysis. Subsequently, case studies highlight successful applications of CADD in the identification and optimization of lead compounds targeting various psychotropic and neurological targets. Finally, the review discusses future prospects and challenges in the field, emphasizing the potential of CADD to expedite the discovery of novel therapeutics for these debilitating disorders.
Keywords: Alzheimer’s disease; Deep Learning; Docking; Ligand-based drug design; QSAR; Schizophrenia; Structure-based drug design; Virtual screening; artificial intelligence; computer-aided drug design; molecular dynamics; neurological; neuropathic pain; pharmacophore; psychotropic